2019
DOI: 10.1186/s40425-019-0636-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative safety and efficacy of anti-PD-1 monotherapy, chemotherapy alone, and their combination therapy in advanced nasopharyngeal carcinoma: findings from recent advances in landmark trials

Abstract: Recent phase 1–2 trials reported manageable safety profiles and promising antitumor activities of anti-PD-1 drugs (pembrolizumab, nivolumab, camrelizumab and JS001) with/without chemotherapy in recurrent/metastatic nasopharyngeal carcinoma (RM-NPC), however head-to-head comparison among these regimens is lacking. We aimed to comprehensively compare the efficacy and safety of different anti-PD-1 drugs, standard chemotherapy, and their combination therapy in RM-NPC. Adverse event (AE) and objective response rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 14 publications
4
49
0
4
Order By: Relevance
“…26 This review differs from previous articles by providing a comprehensive analysis of both current and future immunotherapy NPC trials. 18,29…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 This review differs from previous articles by providing a comprehensive analysis of both current and future immunotherapy NPC trials. 18,29…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…Subtype III, with high expression of T effector genes and high IFNγ signature, may be enriched for potential responders to checkpoint blockade therapy . This review differs from previous articles by providing a comprehensive analysis of both current and future immunotherapy NPC trials …”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the ORRs of nivolumab-treated patients in PD-L1-positive and -negative subgroups were 39.3% (34.1-44.4%) and 22.9% (19.4-26.3%), respectively, while the corresponding rates in pembrolizumabtreated patients were 30.3% (25.2-35.3%) and 10.8% (3.3-18.4%), respectively (90). Moreover, in a pooled analysis of secondor later-line treatment of nasopharyngeal cancer, camrelizumab (34.1%) exhibited the highest ORR, followed by pembrolizumab (26.3%), JS001 (23.3%), and nivolumab (19.0%) (91). Besides, Duan J et al conducted a meta-analysis with an adjusted mirror principal to explore the potential differences in PD-1/PD-L1 inhibitors.…”
Section: Clinical Efficacymentioning
confidence: 93%
“…Moreover, a pooled analysis of nasopharyngeal cancer patients showed that the incidence rates of grade 1-5/3-5 AEs are 74.1/29.6, 54.2/17.4, 92.3/24.5, and 96.8/16.1% for pembrolizumab, nivolumab, JS001, and camrelizumab, respectively. This further indicates that, with respect to grade 1-5 AEs, nivolumab and pembrolizumab may be superior options, but when considering grade 3-5 AEs, camrelizumab and nivolumab show more favorable safety (91).…”
Section: Safetymentioning
confidence: 97%
See 1 more Smart Citation